2008
DOI: 10.1139/t07-108
|View full text |Cite
|
Sign up to set email alerts
|

Consistent preload calculations for jackup spudcan penetration in clays

Abstract: Onshore bearing capacity methods have conventionally been used to predict the penetration of offshore jackup spudcans into the seabed. However, the Brinch Hansen depth factor has a step change in value at the point at which the lateral dimension of a footing equals its embedment. For soft clay seabeds, where penetrations can be greater than the spudcan diameter, the step produces a spurious, unrealistic prediction of punchthrough. A small modification is proposed to the depth factor to avoid this. Some consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Previous studies on spudcan-footprint interaction, however, have not considered the jack-up operational period, or any elapsed time between the initial and final installation (Stewart & Finnie, 2001;Gaudin et al, 2007;Dean, 2008;Gan et al, 2008;Cassidy et al, 2009). In this paper, the duration of the jack-up operational period and the elapsed time between previous spudcan extraction and spudcan reinstallation were systematically investigated using a centrifuge modelling technique.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on spudcan-footprint interaction, however, have not considered the jack-up operational period, or any elapsed time between the initial and final installation (Stewart & Finnie, 2001;Gaudin et al, 2007;Dean, 2008;Gan et al, 2008;Cassidy et al, 2009). In this paper, the duration of the jack-up operational period and the elapsed time between previous spudcan extraction and spudcan reinstallation were systematically investigated using a centrifuge modelling technique.…”
Section: Introductionmentioning
confidence: 99%
“…Later more related works on the use of upper bound method in some tenacious patterns are reported, notably, the work of Bona (2004), Es-Saheb (2004) and Moller et al (2004), as well as Ebrahimi and Najafizadeh (2004). Also, in the civil engineering field, the upper bound method is widely used in predicting and estimating the loads in the foundations and footings of different shapes, as reported in the last few years, by Zhu and Michalowski (2005), Merifield and Nguyen (2006), Gourvenec et al (2006), Gourvenec (2007), Zhang (2008), Dean (2008) and Yilmaz and Bakir (2009) and most recently by Arabshahi et al (2010), as well as Majidi et al (2011) and Veiskarami et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…6,[14][15][16][17][18] However, limited studies in the literature for solving the bearing capacity problems of conical footing have been reported. 19,20 As seen in Figure 1, the jack-up structure is utilized for drilling and maintenance works in the oil and gas industry, 21,22 and each of its legs is standing on spudcan, [23][24][25][26][27][28] which has a diameter ranging from 5 to 20 m. 21,29 With the use of the flat base theory, Meyerhof 30 proposed the bearing capacity theory for the conical footing by conducting the loading tests on cones and indicated that when the wedge angle F I G U R E 1 Jack-up rig model (β) increases, the point resistance of a pile with smooth and rough tips are increased and decreased, respectively. By solving the differential equations derived from the combination of the equilibrium equation and yield condition, Houlsby 31 computed the ultimate load of the wedge-shaped footing with the cone test of clayey soil, and the author found that the bearing capacity is considerably influenced by the wedge angle.…”
Section: Introductionmentioning
confidence: 99%